2014
DOI: 10.1007/s10811-014-0456-6
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate enhances phlorotannin production in the brown seaweed Ecklonia cava

Abstract: Ecklonia cava is a brown seaweed widely distributed on the coasts of Korea and Japan and is used as food ingredient, animal feed, fertilizer, and medicine. E. cava contains a variety of compounds including carotenoids, fucoidans, and phlorotannins that play diverse biological and ecological roles. The marine algal polyphenols, the phlorotannins, found only in the brown algae have greater potential antioxidant activity than the polyphenols from terrestrial plants. Considering their significance in industrial ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…The timing and magnitude of the induced increase in phlorotanin concentration was similar to those caused by real or simulated herbivory, indicating the putative role of MeJA in antiherbivore responses in algae. Recently, Chowdhury et al (2014) also showed that the addition of 2 mM MeJA for 24 h to post-harvest cultures of Ecklonia cava increased the crude phlorotanin (brown algal polyphenol) content by 156%. In contrast, Collén et al (2006) found that only the transcripts for DHAP (3-deoxy-D-arabino-heptulosonic acid-7-phosphate) synthase in a C. crispus microarray was overexpressed at 6 h, while no other transcripts involved in the shikimate pathway were identified.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and magnitude of the induced increase in phlorotanin concentration was similar to those caused by real or simulated herbivory, indicating the putative role of MeJA in antiherbivore responses in algae. Recently, Chowdhury et al (2014) also showed that the addition of 2 mM MeJA for 24 h to post-harvest cultures of Ecklonia cava increased the crude phlorotanin (brown algal polyphenol) content by 156%. In contrast, Collén et al (2006) found that only the transcripts for DHAP (3-deoxy-D-arabino-heptulosonic acid-7-phosphate) synthase in a C. crispus microarray was overexpressed at 6 h, while no other transcripts involved in the shikimate pathway were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of dieckol, phlorotannin 974B, phlorotannin 974A, and phlorofucofuroeckol-A from ethyl ether fraction of crude extract [188].…”
Section: Luna-c18 (-)mentioning
confidence: 99%
“…Reversed-phase (RP) HPLC columns have been the most used in macroalgae phenolic rich extracts [32,39,62,73,157,159,169,173,180,182,[186][187][188][189]. Octadecyl ("C18" or "ODS") has been the most used stationary phase, with a particle size of 5 µm.…”
mentioning
confidence: 99%
See 1 more Smart Citation